Antioxidant, analgesic and anti-inflammatory activities of the methanolic extract of Piper betle leaves - Alam, Badrul (Mashhad University of Medical Sciences, 2013)
Objective: The present study was designed to evaluate the antioxidant, analgesic, and anti-inflammatory activities of the methanolic extract of Piper betle leaves (MPBL). Materials and Methods: MPBL was evaluated for anti-inflammatory activity using carrageenan-induced hind paw edema model. Analgesic activity of MPBL was evaluated by hot plate, writhing, and formalin tests. Total phenolic and flavonoids content, total antioxidant activity, scavenging of 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical, peroxynitrate (ONOO) as well as inhibition of total ROS generation, and assessment of reducing power were used to evaluate antioxidant potential of MPBL. Results: The extract of MPBL, at the dose of 100 and 200 mg/kg, produced a significant (p<0.05) increase in pain threshold in hot plate method whereas significantly (p<0.05) reduced the writhing caused by acetic acid and the number of licks induced by formalin in a dose-dependent manner. The same ranges of doses of MPBL caused significant (p<0.05) inhibition of carrageenan-induced paw edema after 4 h in a dose-dependent manner. In DPPH, ONOO(-), and total ROS scavenging method, MPBL showed good antioxidant potentiality with the IC(50) value of 16.33±1.02, 25.16±0.61 , and 41.72±0.48 µg/ml, respectively with a significant (p<0.05) good reducing power. Conclusion: The findings of the study suggested that MPBL has strong analgesic, anti-inflammatory, and antioxidant effects, conforming the traditional use of this plant for inflammatory pain alleviation to its antioxidant potentiality.